2008
DOI: 10.1055/s-2008-1065015
|View full text |Cite
|
Sign up to set email alerts
|

Alkalische Knochenphosphatase als Aktivitätsparameter der Akromegalie

Abstract: Serum levels of growth hormone (GH: arithmetic mean of three measurements eight hours apart), somatomedin C (SmC), alkaline phosphatase activity and the bone isoenzyme of alkaline phosphatase (as the liver/bone isoenzyme ratio) were measured in 26 patients with acromegaly (11 men and 15 women; mean age 45.5 [24-66] years), 18 in the active and eight in the nonactive phase of the disease. Activity was characterized by a raised (660 [330-1149] ng/ml), inactivity by a normal (186 [40-300] ng/ml) SmC concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Our study agrees with previous studies in significant elevated GOT, GPT and ALP activity levels in acromegalic patients. Another study showed that pituitary surgery in patients with acromegaly led to significant decrease in GPT levels (29) .…”
Section: Association Of Vitamin D With Liver Function (Got Gpt and Alp)mentioning
confidence: 99%
“…Our study agrees with previous studies in significant elevated GOT, GPT and ALP activity levels in acromegalic patients. Another study showed that pituitary surgery in patients with acromegaly led to significant decrease in GPT levels (29) .…”
Section: Association Of Vitamin D With Liver Function (Got Gpt and Alp)mentioning
confidence: 99%